2017
DOI: 10.1021/jacs.7b00319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition-Based DNA Nanoassemblies on the Surfaces of Nanosized Exosomes

Abstract: Exosomes are membrane-enclosed extracellular vesicles derived from cells, carrying biomolecules that include proteins and nucleic acids for intercellular communication. Owning to their advantages of size, structure, stability, and biocompatibility, exosomes have been used widely as natural nanocarriers for intracellular delivery of theranostic agents. Meanwhile, surface modifications needed to endow exosomes with additional functionalities remain challenging by their small size and the complexity of their memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 33 publications
1
165
0
Order By: Relevance
“…For flow cytometry (FCM) and confocal imaging,the exosomes were adsorbed on aldehyde latex microspheres. [19] Thes ignal of CD63 (a common exosomal biomarker) was obvious ( Figure S7), indicating that exosomes were successfully modified onto the microspheres.F or exosomal PD-L1 recognition, the fluorescence enhancement of the MJ5C aptamer binding (compared to control sequence) was about 5t imes higher than that of the antibody (compared to control protein;F igure 3D), and MJ5C maintained high selectivity and demonstrated no observable binding against PD-L1 negative exosomes ( Figure 3E). Furthermore,c onfocal results indicated that some fluorescent spots were distributed on the surface of the PD-L1 positive microspheres,w hich came from the binding of the fluorescent labeled aptamer ( Figure 3D).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For flow cytometry (FCM) and confocal imaging,the exosomes were adsorbed on aldehyde latex microspheres. [19] Thes ignal of CD63 (a common exosomal biomarker) was obvious ( Figure S7), indicating that exosomes were successfully modified onto the microspheres.F or exosomal PD-L1 recognition, the fluorescence enhancement of the MJ5C aptamer binding (compared to control sequence) was about 5t imes higher than that of the antibody (compared to control protein;F igure 3D), and MJ5C maintained high selectivity and demonstrated no observable binding against PD-L1 negative exosomes ( Figure 3E). Furthermore,c onfocal results indicated that some fluorescent spots were distributed on the surface of the PD-L1 positive microspheres,w hich came from the binding of the fluorescent labeled aptamer ( Figure 3D).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The Tan group, for example, developed a sensor for electrochemical detection of cancerous exosomes . In that work, they introduced a aptamer, named LZH8, that could specifically recognize HepG2 (hepatocarcinoma cells) and their exosomes . As shown in Figure , aptamer LZH8 was attached to a DNA nanotetrahedron (NTH).…”
Section: Applications Of Exosomesmentioning
confidence: 99%
“…[59] In that work, they introduced aa ptamer,n amed LZH8,t hat could specifically recognize HepG2 (hepatocarcinoma cells) andt heir exosomes. [60] As shown in Figure 5, aptamer LZH8 was attached to aD NA nanotetrahedron (NTH). Subsequently,t he NTH sequences werei mmobilizedo ntot he surfaces of Au electrodes.…”
Section: Exosomes In Cancer Detectionmentioning
confidence: 99%
“…[44,52,[62][63][64] 3. Non-enzymatic and Isothermal Signal Amplification Techniques Dynamic DNAs elf-assembly (DDSA) is fueled by the free energy of hybridization between metastable DNAh airpins or driven by the entropy of hybridization between linear DNAm olecules, [63,[65][66][67][68][69][70][71][72][73] and can operate in an autonomous and reconfigurable manner.F or instance,t he hybridization chain reaction (HCR) was first proposed by the Pierce group in 2004 ( Figure 1A). [63] Tw om etastable DNAh airpin monomers coexist in solution, only upon exposure to an initiator nucleic acid fragment, HCR is triggered and the monomers sequentially assemble to form al ong double-stranded DNA analogue with nicking sites.S ubsequently,t hey developed anew DDSA technique,which they termed catalyzed hairpin assembly (CHA) or catalytic assembly circuit (CAC) ( Figure 1B).…”
Section: Traditional Amplification-based Detection Of Rnamentioning
confidence: 99%